Polyolefin composition obtained from recycled polyolefin
By designing a polypropylene composition containing propylene homopolymer and recycle composition, the sustainability of existing polyolefin compositions has been solved, and performance improvements and sustainable development of materials have been achieved.
Patent Information
- Application Number
- CN202380051518.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2023-07-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-07-26
AI Technical Summary
Existing polyolefin compositions have problems with sustainability, especially since their production relies on non-renewable resources and the difficulty in quantitative separation of recycled polymers, resulting in contamination and degradation of performance.
The impact and modulus values of the material are improved by the design of the composition including 50 wt% to 80 wt% propylene homopolymer or propylene ethylene copolymer and 20 wt% to 50 wt% blends, which include 20 wt% to 80 wt% recycled composition and 20 wt% to 80 wt% recycled polyethylene.
Improved characteristic curves are achieved, especially in terms of impact and modulus values, improving the performance of the material, while reducing dependence on non-renewable resources, and enhancing the sustainability of the material.
Smart Images

Figure BDA0005225268810000111 
Figure BDA0005225268810000112
Abstract
Description
Technical Field
[0001] The present disclosure relates to soft polypropylene compositions comprising recycled elastomeric materials useful for preparing extruded articles. Background Art
[0002] Due to the valuable properties typical of polyolefins, such as chemical inertness, mechanical properties and non-toxicity, polyolefin compositions with elasticity while maintaining good thermoplastic behavior have been used in many application areas. In addition, they can be advantageously converted into finished products using the same techniques used for thermoplastic polymers. In particular, flexible polymer materials are widely used in the medical field, as well as for packaging, extrusion coating and wire and cable covering.
[0003] Elastic polypropylene compositions retaining good thermoplastic behavior have been obtained in the art by sequential copolymerization of propylene, optionally containing small amounts of olefin comonomers, and then ethylene / propylene or ethylene / α-olefin copolymer mixtures. Catalysts based on halogenated titanium compounds supported on magnesium chloride are generally used for this purpose. For example, EP-A-472 946 describes a flexible elastoplastic polyolefin composition comprising, in parts by weight: A) 10 to 50 parts of isotactic propylene homopolymer or copolymer; B) 5 to 20 parts of an ethylene copolymer insoluble in xylene at room temperature; and C) 40 to 80 parts of an ethylene / propylene copolymer containing less than 40 wt% of ethylene and soluble in xylene at room temperature; the intrinsic viscosity of the copolymer is preferably from 1.7 to 3 dl / g. The composition is relatively flexible and has good elasticity.
[0004] Furthermore, polyolefin compositions, although appreciated in terms of performance, raise concerns in terms of sustainability, in particular with reference to the fact that their production is based on the use of non-renewable resources.
[0005] Therefore, a common attempt to alleviate this problem is to at least partially replace the virgin polyolefin composition with variable amounts of recycled plastic material.
[0006] Recycled plastic polyolefins are derived from post-consumer waste (PCW) or post-industrial waste (PIW) streams.
[0007] One of the key problems in polyolefin recycling is the difficulty in quantitatively separating the various types of polymers, so that commercially available recycled products are almost always contaminated with heterogeneous materials from various sources.
[0008] This fact results in the fact that polymer compositions comprising recycled materials are believed to suffer from lower reliability and lower performance relative to compositions made from virgin polymer alone.
[0009] It has now surprisingly been found that when a blend of recycled polymers is added to virgin polypropylene, it is possible to have an improved property profile, in particular with regard to impact and modulus values. Summary of the invention
[0010] Therefore, the object of the present disclosure is a propylene polymer composition having a melt flow rate value (ISO 1133-1 230°C / 2.16kg) in the range of 3.0 g / 10 min to 70.0 g / 10 min, comprising:
[0011] A) 50 to 80 wt% of a propylene homopolymer or a propylene ethylene copolymer containing up to 22.0 wt% of ethylene, said propylene homopolymer or propylene ethylene copolymer having a melt flow rate in the range of 20.0 to 100.0 g / 10 min (ISO 1133-1 230°C / 2.16 kg);
[0012] B) 50 wt% to 20 wt% of a blend comprising:
[0013] T1) 20 wt% to 80 wt% of a recycled composition comprising:
[0014] (T1a) at least 70 wt% of a propylene copolymer containing from 1 wt% to 15 wt% of ethylene;
[0015] (T1b) 5 wt% to 30 wt% of a styrenic block copolymer (SBC), and optionally,
[0016] (T1c) 1 to 15 wt% of an ethylene homopolymer or copolymer containing up to 30 wt% of C3-C 10 α-olefins;
[0017] The sum of the amounts of T1a, T1b, and T1c is 100;
[0018] T2) 20 wt% to 80 wt% recycled polyethylene (r-PE) having a melt flow rate (190°C / 2.16 kg) of 0.1 to 10.0 g / 10 min and containing a polypropylene content in an amount ranging from 1 to 15 wt% of the total r-PE component,
[0019] The sum of the amounts of T1 and T2 is 100;
[0020] The sum of the quantities of A) and B) is 100. DETAILED DESCRIPTION
[0021] The object of the present disclosure is a propylene polymer composition having a melt flow rate value (ISO 1133-1 230°C / 2.16kg) in the range of 3.0 g / 10min to 70.0 g / 10min; preferably 15.0 g / 10min to 45.0 g / 10min; more preferably 20.0 g / 10min to 35.0 g / 10min, comprising or consisting essentially of:
[0022] A) 50 wt% to 80 wt%, preferably 55 wt% to 75 wt%; more preferably 58 wt% to 72 wt%; even more preferably 55 to 65 wt% of a propylene homopolymer or a propylene ethylene copolymer containing up to 22.0 wt%; preferably up to 12.0 wt%; more preferably up to 7.0 wt% of ethylene, the propylene homopolymer or the propylene ethylene copolymer having a melt flow rate (ISO 1133-1230°C / 2.16kg) in the range of 20.0 to 100.0 g / 10 min, preferably 60.0 to 90.0 g / 10 min; more preferably 65.0 to 85.0 g / 10 min;
[0023] B) 20 wt% to 50 wt%, preferably 25 wt% to 45 wt%; more preferably 28 wt% to 42 wt%; even more preferably 35 wt% to 45 wt% of a blend comprising:
[0024] T1) 20 wt% to 80 wt%; preferably 25 wt% to 75 wt%; more preferably 28 wt% to 55 wt% of a recycled composition comprising:
[0025] (T1a) at least 70 wt%, preferably 75 to 90 wt%, of a propylene copolymer containing 1 to 15 wt%, preferably 1 to 7 wt%, of ethylene;
[0026] (T1b) 5 wt% to 30 wt%, preferably 7 wt% to 25 wt% of a styrenic block copolymer (SBC), and optionally,
[0027] (T1c) 1 to 15 wt%, preferably 2 to 4 wt%, of an ethylene homopolymer or copolymer containing up to 30 wt% of C3-C 10 α-Olefins.
[0028] The sum of the amounts of T1a, T1b, and T1c is 100;
[0029] T2) 20 wt% to 80 wt%; preferably 25 wt% to 75 wt%, more preferably 28 wt% to 72 wt% of recycled polyethylene (r-PE) having a melt flow rate (190°C / 2.16 kg) of 0.1 to 10 g / 10 min and containing a polypropylene content in an amount ranging from 1 wt% to 15 wt% of the total r-PE component;
[0030] The sum of the amounts of T1 and T2 is 100;
[0031] The sum of the quantities of A) and B) is 100.
[0032] As used herein, the term "copolymer" refers to polymers having two different repeating units in the chain and polymers having more than two different repeating units, such as terpolymers. "Ambient or room temperature" herein refers to a temperature of 25°C.
[0033] The term "crystalline propylene polymer" as used herein refers to a propylene polymer having an amount of isotactic pentads (mmmm) greater than 70 mol %, said amount being determined by 13 C-MNR measures the fraction insoluble in xylene at 25°C; an "elastomeric" polymer is one whose solubility in xylene at ambient temperature is greater than 50 wt%.
[0034] The term "consisting essentially of" as used herein in conjunction with a polymer or polymer composition means that in addition to the mandatory ones, other components may also be present in the polymer or polymer composition, provided that the basic characteristics of the polymer or composition are not substantially affected by their presence. Examples of components that do not substantially affect the properties of a polymer or polymer composition when present in conventional amounts according to the present disclosure are catalyst residues, antistatic agents, melt stabilizers, light stabilizers, antioxidants, antacids.
[0035] The features of the components forming the polypropylene composition are not excessively connected to each other. This means that a certain preference of a feature does not necessarily relate to the same preference of the remaining features of the same or different components. On the contrary, it is intended in the present disclosure that any component (A) to (B) and any preferred range of the features of component (A) to (B) can be combined with any preferred range of one or more features of component (A) to (B) and with any possible additional components and their features described in the present disclosure.
[0036] Preferably, component A) is a pure resin; preferably, component A is a propylene homopolymer.
[0037] The melting temperature of component A) preferably ranges from 135 to 165° C. When component A) is a homopolymer, the melting temperature determined by DSC is preferably from 155 to 165° C., while for copolymers it is preferably from 135 to 155° C.
[0038] Component A) can be prepared by polymerizing propylene, optionally in a mixture with ethylene, in the presence of a catalyst comprising the reaction product between:
[0039] i) a solid catalyst component comprising Ti, Mg, Cl and at least one internal electron donor compound;
[0040] ii) an alkylaluminum compound and,
[0041] iii) external electron donor compounds having the following general formula:
[0042] (R 7 ) a (R 8 ) b Si(OR 9 )c, wherein a and b are integers from 0 to 2, c is an integer from 1 to 4 and the sum (a+b+c) is 4; and R 7 , R 8 and R 9 is an alkyl, cycloalkyl or aryl group having 1 to 18 carbon atoms, optionally containing heteroatoms.
[0043] The internal donor is preferably selected from esters of mono- or dicarboxylic organic acids, such as benzoates, malonates, phthalates and certain succinates. Examples of internal donors are described in US 4522930A, EP 045977A2 and international patent applications WO 00 / 63261 and WO 01 / 57099. Particularly suitable are phthalates and succinates. Alkyl phthalates are preferred, such as diisobutyl phthalate, dioctyl phthalate and diphenyl phthalate and benzyl butyl phthalate.
[0044] The particles of solid component (i) have a substantially spherical morphology and an average diameter in the range of 5 to 150 μm, preferably 20 to 100 μm and more preferably 30 to 90 μm. As particles having a substantially spherical morphology, it is meant that the ratio between the major axis and the minor axis is equal to or lower than 1.5, and preferably lower than 1.3.
[0045] The amount of Mg may preferably range from 8 to 30%, more preferably from 10 to 25 wt%.
[0046] The amount of Ti may be 0.5 to 7 wt%, more preferably 0.7 to 5 wt%.
[0047] According to one method, the solid catalyst component (i) can be prepared by reacting a titanium compound of the formula Ti(OR)q-yXy (where q is the valence of titanium and y is a number between 1 and q, preferably TiCl4) with a magnesium chloride derived from an adduct of the formula MgCl2·pROH (where p is a number between 0.1 and 6, preferably 2 to 3.5, and R is a hydrocarbon group having 1 to 18 carbon atoms). The adduct can be suitably prepared in spherical form by mixing an alcohol and magnesium chloride, operating under stirring conditions at the melting temperature of the adduct (100-130°C). The adduct is then mixed with an inert hydrocarbon immiscible with the adduct, thereby producing an emulsion, which is rapidly quenched, causing the adduct to solidify in the form of spherical particles. Examples of spherical adducts prepared according to this procedure are described in USP 4,399,054 and USP 4,469,648. The adduct thus obtained can be reacted directly with the Ti compound, or it can be previously subjected to a thermally controlled dealcoholation (80-130° C.) to obtain an adduct in which the number of moles of alcohol is less than 3, preferably 0.1-2.5. The reaction with the Ti compound can be carried out by suspending the adduct (dealcoholated or as such) in cold TiCl4; heating the mixture to 80-130° C. and keeping it at this temperature for 0.5-2 hours. The treatment with TiCl4 can be carried out once or more. The electron donor compound can be added during the treatment with TiCl4 in the desired ratio.
[0048] The alkyl-Al compound (ii) is preferably selected from trialkylaluminum compounds, such as triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum. It is also possible to use alkylaluminum halides, alkylaluminum hydrides or alkylaluminum sesquichlorides, such as AlEt2Cl and Al2Et3Cl3, which may be mixed with the above trialkylaluminums. The Al / Ti ratio is higher than 1 and may preferably be in the range between 50 and 2000.
[0049] Particularly preferred are silicon compounds (iii) wherein a is 1, b is 1, c is 2, R 7 and R 8At least one of them is selected from a branched alkyl, cycloalkyl or aryl group having 3 to 10 carbon atoms, optionally containing heteroatoms, and R9 is a C1-C10 alkyl group, in particular a methyl group. Examples of such preferred silicon compounds are methylcyclohexyldimethoxysilane (C donor), diphenyldimethoxysilane, methyl tert-butyldimethoxysilane, dicyclopentyldimethoxysilane (D donor), diisopropyldimethoxysilane, (2-ethylpiperidinyl) tert-butyldimethoxysilane, (2-ethylpiperidinyl) tert-hexyldimethoxysilane, (3,3,3-trifluoro-n-propyl) (2-ethylpiperidinyl) dimethoxysilane, methyl (3,3,3-trifluoro-n-propyl) dimethoxysilane. In addition, the following silicon compounds are also preferred, wherein a is 0, c is 3, R8 is a branched alkyl or cycloalkyl group optionally containing heteroatoms, and R9 is methyl. Examples of such preferred silicon compounds are cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane and tert-hexyltrimethoxysilane.
[0050] The external electron donor compound (iii) is used in such an amount that the molar ratio of the organoaluminium compound to said external electron donor compound (iii) is from 0.1 to 200, preferably from 1 to 100, more preferably from 3 to 50.
[0051] The polymerization process can be carried out in the gas phase, operating in one or more fluidized or mechanically stirred bed reactors, slurry polymerization using an inert hydrocarbon solvent as a diluent, or bulk polymerization using a liquid monomer (e.g. propylene) as a reaction medium. If desired, component A can be chemically treated with an organic peroxide to reduce the average molecular weight and increase the melt flow index to the value required for a specific application.
[0052] Component (T1) may be derived from post-consumer waste (PostCW) or from pre-consumer waste (Pre-CW). Preferably, it is derived from Pre-CW. Pre-consumer plastic is considered to be plastic waste diverted from the manufacturing process, which is not reused, such as reprocessed, regrind or scrap, and is not recombined in the same process that produced it.
[0053] Component (T1a) is preferably a propylene random copolymer containing 1 to 6 wt%, preferably 2 to 5 wt% ethylene. It can be obtained, for example, from pre-consumer random PP material used for packaging.
[0054] Component (T1b) is preferably selected from SBS and SEBS rubbers, which are (partially) hydrogenated styrene-(ethylene-butadiene)-styrene block copolymers. These polymers are triblock copolymers having styrene and internal polybutadiene or ethylene / butadiene, polyisoprene or hydrogenated polybutadiene or polyisoprene blocks at both ends of the polymer chain.
[0055] SBC copolymers are obtained by anionic polymerization and are commercially available, for example, under the trade names of Kraton and Tuftec, for example Kraton SEBS G1657MS. It is also preferred that component (T1b) is derived from a pre-consumer source.
[0056] Preferably, component (T1c) is present in an amount ranging from 1 wt% to 5 wt%, preferably from 2 wt% to 4 wt%. It preferably contains up to 30 wt%, preferably up to 20 wt%, more preferably up to 15 wt% of C3-C 10 Ethylene polymers of alpha olefins. Preferably, the alpha olefin is selected from butene-1, hexene-1 and octene-1.
[0057] The ethylene polymer is preferably selected from LDPE, LLDPE, VLDPE and polyolefin elastomers (POE) of pre-consumer origin.
[0058] The melt flow rate (ISO 1133-1 230° C. / 2.16 kg) of the entire component (T1) may generally range from 0.5 to 30.0 g / 10 min, preferably from 1.0 to 25.0 g / 10 min, more preferably from 2.0 to 20.0 g / 10 min.
[0059] Component (T1) according to the present disclosure preferably has a tensile modulus below 500 MPa, preferably below 400 MPa.
[0060] The component (T1) of the present disclosure preferably has a thermal conductivity of 50 to 100 kJ / m 2 , more preferably 55 to 80 kJ / m 2 The Charpy impact strength at 23°C is preferably in the range of 5 to 20 kJ / m 2 , more preferably 6 to 15 kJ / m 2 .
[0061] Component (T1) of the present disclosure may exhibit an elongation at break equal to or higher than 400%, more preferably in the range of 500 to 600%.
[0062] The melting temperature of component (T1) ranges from 140°C to 160°C, preferably from 145°C to 155°C.
[0063] Component (T2) is a recycled polyethylene PE, which is preferably a crystalline or semi-crystalline high density PE (r-HDPE) selected from commercial PCW (e.g. post-consumer waste from municipalities). Preferably, the r-PE has a density of 0.940 g / cm 3 Up to 0.965g / cm 3The density (ISO 1183-1) and the melt flow rate (190°C / 2.16Kg ISO 1133-1) of 0.1 to 1.0 g / 10 min.
[0064] Prior to its use, the plastic mixture containing rHDPE undergoes a standard recycling process, including collection, shredding, sorting and washing. Although the sorted rHDPE is composed of a large amount of HDPE, it always contains a small amount of other polymers and / or inorganic components. In particular, the r-PE according to the present disclosure contains a polypropylene content in an amount of 1 wt% to 15 wt%, preferably 5 wt% to 10 wt% of the total r-PE component.
[0065] In a preferred embodiment, the r-PE comprises a crystalline polyethylene portion, wherein the amount of repeating units derived from propylene in the polyethylene chain is less than 10 wt% and most preferably they are absent, i.e. most preferably the r-PE is an ethylene homopolymer containing the above inclusions. Preferably, the melt flow rate (190°C / 2.16 kg ISO 1133-1) of (r-PE) is from 0.1 to 1.0 g / 10 min, more preferably from 0.1 to 0.5 g / 10 min.
[0066] r-PE is commercially available. An example of a suitable r-PE grade is represented by the grade sold by Lyondellbasell under the trade name Hostalen QCP5603 in ivory or grey.
[0067] The overall polypropylene composition of the present disclosure preferably shows lower tensile modulus values than component A). In a preferred embodiment, the overall propylene polymer composition has a tensile modulus in the range of 750 MPa to 1700 MPa, more preferably in the range of 800 to 1500 MPa.
[0068] The Charpy impact value range at 23°C is 20.0Kj / m 2 Up to 3.0Kj / m 2 ; The Charpy impact value range at 0℃ is 2.0Kj / m 2 Up to 14.0Kj / m 2 ; The Charpy impact value range at -20℃ is 1.0Kj / m 2 Up to 10.0Kj / m 2 .
[0069] The overall propylene composition of the present disclosure can be obtained by mechanically blending components (A)-(B) according to conventional techniques.
[0070] The final composition comprising components (A)-(B) can be added together with conventional additives, fillers and pigments commonly used in olefin polymers such as nucleating agents, extender oils, mineral fillers and other organic and inorganic pigments. In particular, the addition of inorganic fillers such as talc, calcium carbonate and mineral fillers also brings about improvements in some mechanical properties such as flexural modulus and HDT. Talc can also have a nucleating effect.
[0071] For example, the nucleating agent may be added to the composition of the present disclosure in an amount ranging from 0.05 to 2 wt %, more preferably from 0.1 to 1 wt %, relative to the total weight.
[0072] The propylene polymer composition of the present disclosure can be extruded to form films or sheets for various applications. Particularly preferred is the use of the polypropylene composition for the preparation of sheets for roofing applications.
[0073] The following examples are given to illustrate but not to limit the present disclosure.
[0074] Example
[0075] Characterization
[0076] Xylene soluble (XS) fraction at 25°C
[0077] 2.5g polymer and 250ml xylene are introduced into a glass flask equipped with a refrigerator and a magnetic stirrer. The temperature is raised to the boiling point of the solvent within 30 minutes. The clear solution thus obtained is then kept at reflux and stirred for another 30 minutes. The closed flask is then kept in an ice-water bath for 30 minutes and then in a 25°C constant temperature water bath for 30 minutes. The solid obtained is filtered on a quick filter paper. 100ml of the filtrate is poured into a pre-weighed aluminum container, which is heated on a heating plate in a nitrogen stream to remove the solvent by evaporation. The container is then kept in an oven at 80°C under vacuum until constant weight is obtained. The weight percentage of the polymer soluble in xylene at room temperature is then calculated.
[0078] The content of the xylene soluble fraction is expressed as a percentage of the original 2.5 g, and the xylene insoluble percentage (%) is then expressed by difference (complementary to 100%);
[0079] Melt flow rate (MFR)
[0080] According to ISO 1133-1, measured at 190°C or 230°C under a load of 2.16 kg, as specified.
[0081] Intrinsic viscosity (IV)
[0082] The sample is dissolved in tetralin at 135°C and poured into a capillary viscometer. The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass sleeve; the setup allows temperature control using a circulating thermostatic liquid. The downward passage of the meniscus is timed by a photoelectric device.
[0083] The passage of the meniscus in front of the upper lamp starts a counter with a quartz crystal oscillator. The meniscus stops the counter when it passes the lower lamp and the discharge time is recorded: If the flow time of the pure solvent is known under the same experimental conditions (same viscometer and same temperature), it can be converted into an intrinsic viscosity value by the Huggins equation (Huggins, ML, J. Am. Chem. Soc., 1942, 64, 2716). A single polymer solution is used to determine [η].
[0084] Polydispersity Index : measured by using a parallel plate rheometer of type RMS-800 sold by RHEOMETRICS (USA) at a temperature of 200°C, operating at an oscillation frequency increasing from 0.1 rad / sec to 100 rad / sec. From the crossover modulus, PI can be obtained by the following equation:
[0085] PI=105 / Gc
[0086] Where Gc is the crossover modulus, which is defined as the value (expressed in Pa) when G'=G", where G' is the storage modulus and G" is the loss modulus.
[0087] Ethylene (C2) content
[0088] Propylene / ethylene copolymer 13 C NMR
[0089] 13 C NMR spectra were obtained on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating at 160.91 MHz in Fourier transform mode at 120 °C.
[0090] At 29.9ppm S ββThe peak of carbon (according to the nomenclature of "Monomer sequence distribution in ethylene-propylene rubber measured by 13C NMR. 3. Use of reaction probability models" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, 10, 536) was used as an internal reference. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at 8 wt / v% concentration at 120°C. Each spectrum was obtained with a 90° pulse and a delay of 15 seconds between the pulse and CPD to remove 1H-13C coupling. 512 transients were stored in 32K data points using a spectral window of 9000 Hz.
[0091] Evaluation of spectral assignments, triplet distribution, and composition was performed according to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titanium trichloride-diethylaluminum chloride" M. Kakugo, Y. Naito, K. Mizunuma, and T. Miyatake, Macromolecules, 1982, 15, 4, 1150–1152) using the following equation:
[0092] PPP=100T ββ / S PPE=100T βδ / S EPE=100T δδ / S
[0093] PEP=100s ββ / S PEE=100S βδ / S EEE=100(0.25S γδ +0.5S δδ ) / S
[0094] S=T ββ +T βδ +T δδ +S ββ +S βδ +0.25S γδ +0.5S δδ
[0095] The mole percent of ethylene content was estimated using the following equation:
[0096] E%mol=100*[PEP+PEE+EEE] The weight percentage of ethylene content is estimated using the following equation:
[0097]
[0098] Where P mol% is the molar percentage of propylene content, and MW E and MW P are the molecular weights of ethylene and propylene respectively.
[0099] According to Carman (CJ Carman, RA Harrington and CE Wilkes, Macromolecules 1977; 10, 536), the product of the reaction ratios r1r2 is calculated as:
[0100]
[0101] The stereoregularity of the propylene sequence is determined by PPP mmT ββ (28.90-29.65ppm) and the entire T ββ The ratio of (29.80-28.37ppm) was calculated as the mm content.
[0102] density
[0103] Measured according to ISO 1183-1.
[0104] Samples for mechanical testing
[0105] The samples were obtained according to ISO 1873-2:2007.
[0106] Charpy impact test according to ISO 179-1eA and ISO 1873-2
[0107] Elongation at Yield: Measured according to ISO 527.
[0108] Elongation at break: measured according to ISO 527
[0109] Breaking stress: measured according to ISO 527.
[0110] Tensile modulus according to ISO 527-2
[0111] Tear resistance on 1 mm thick extruded sheets according to method ASTM D 1004. Crosshead speed: 51 mm / min; V-die cut specimens.
[0112] Shore D according to method ISO 868 (15 seconds) on injection molded, compression molded plaques and extruded sheets
[0113] Melting point and crystallization point
[0114] Melting points are measured using a DSC instrument according to ISO 11357-3, at a scan rate of 20° C. / min in cooling and heating, on samples weighing between 5 and 7 mg, under an inert N 2 flow. Indium is used for instrument calibration.
[0115] Determination of PP content in r-PE
[0116] 13 C NMR spectra were obtained on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating at 160.91 MHz in Fourier transform mode at 120 °C.
[0117] The peak of CH2 ethylene was used as an internal standard at 29.9 ppm. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at 8 wt / v% concentration at 120 °C. A 90° pulse was used with a delay of 15 seconds between the pulse and CPD to remove 1 H- 13 Each spectrum was acquired with C coupling. 512 transients were stored in 32K data points using a spectral window of 9000 Hz.
[0118] The molar composition was obtained using the peak areas as follows (Table 1):
[0119] P=100A3 / S
[0120] E=100 0.5A2 / S
[0121] Where S = 0.5A2 + A3
[0122] Monomer molecular weights were used to convert molar contents by weight.
[0123] Table 1: Distribution of PP / PE blends
[0124] Number Chemical shift (ppm) carbon sequence 1 48.8-45.4 <![CDATA[CH2]]> P 2 29.9 <![CDATA[CH2]]> E 3 29.0-28.0 CH P 4 21.8-19.8 CH3 P
[0125] Component A)
[0126] Component A) is a commercial homopolymer sold by Lyondellbasell as HA840R. The homopolymer has been visbroken with peroxide to achieve an MFR of 70 g / 10 min.
[0127] Component T1)
[0128] Component T1 is a recycled composition prepared separately and having an MFR of 4.3 g / 10 min, made of 80 wt% recycled random propylene ethylene copolymer containing 4.5% ethylene, 15% recycled SEBS and 5% recycled LLDPE.
[0129] Component T2
[0130] Component T2 has a viscosity of 0.95 g / cm 3 Commercial grade QCP5603 Ivory (r-PE commercialized by Lyondellbasell, containing 10 wt% PP content) with a density of 0.05 g / 10 min and a melt index "E" of 0.3 g / 10 min.
[0131] Example 1
[0132] The polymer granules of component A) were introduced into an extruder (Berstorff extruder) where they were mixed with the various amounts of components T1 and T2 reported in Table 2, 1000 ppm of MS168 having been added as an additive. The polymer granules were extruded in a twin-screw extruder under a nitrogen atmosphere at a rotation speed of 250 rpm and a melt temperature of 200-250° C. The characterization of the resulting compositions is reported in Table 2.
[0133] Table 2
[0134] Example 1 Example 2 Component A 60 70 Component B 40 30 Component T1 (in B) 30 30 Component T2 (in B) 70 70 MFR, g / 10min 22.2 29.3 Tm℃ 160.6 161.3 Tc℃ 118.9 119.7 <![CDATA[Tensile modulus; (N / mm 2 )]]> 1100 1220 <![CDATA[Charpy impact at 23 °C Kj / m 2 > 10.4 9.8 <![CDATA[Charpy impact at 0 °C Kj / m 2 > 6.3 5.9 <![CDATA[Charpy impact - 20 °C Kj / m 2 > 4.5 3.8 D / T TT℃ ≤-50 ≤-50
Claims
1. A propylene polymer composition having a melt flow rate value (ISO 1133-1 230°C / 2.16kg) in the range of 3.0 g / 10 min to 70.0 g / 10 min, comprising: A) 50 to 80 wt% of a propylene homopolymer or a propylene ethylene copolymer containing up to 22.0 wt% of ethylene, said propylene homopolymer or propylene ethylene copolymer having a melt flow rate in the range of 20.0 to 100.0 g / 10 min (ISO 1133-1 230°C / 2.16 kg); B) 50 wt% to 20 wt% of a blend comprising: T1) 20 wt% to 80 wt% of a recycled composition comprising: (T1a) at least 70 wt% of a propylene copolymer containing from 1 wt% to 15 wt% of ethylene; (T1b) 5 wt% to 30 wt% of a styrenic block copolymer (SBC), and optionally, (T1c) 1 wt% to 15 wt% of an ethylene homopolymer or copolymer containing up to 30 wt% of C3-C 10 α-olefins; The sum of the amounts of T1a, T1b, and T1c is 100; T2) 20 wt% to 80 wt% recycled polyethylene (r-PE) having a melt flow rate (190°C / 2.16 kg) of 0.1 to 10.0 g / 10 min and containing a polypropylene content in an amount ranging from 1 to 15 wt% of the total r-PE component; The sum of the amounts of T1 and T2 is 100; The sum of the quantities of A) and B) is 100.
2. The propylene polymer composition according to claim 1, wherein component (A) ranges from 55 wt% to 75 wt%; and component (B) ranges from 25 wt% to 45 wt%.
3. The propylene polymer composition according to claim 1 or 2, wherein T1 ranges from 25 wt% to 75 wt%, and T2 ranges from 25 wt% to 75 wt%; 4. The propylene polymer composition according to any one of the preceding claims, wherein (T1a) ranges from 75 wt% to 90 wt%; (T1b) ranges from 7 wt% to 25 wt%, and optionally, (T1c) ranges from 2wt% to 4wt%.
5. The propylene polymer composition according to any of the preceding claims having a melt flow rate (ISO 1133-1 230°C / 2.16kg) in the range of 15.0 g / 10 min to 45.0 g / 10 min.
6. The propylene polymer composition according to any one of the preceding claims, wherein (A) has a melt flow rate in the range of 60.0 to 90.0 g / 10 min.
7. The propylene polymer composition according to any of the preceding claims, wherein component (A) is a propylene homopolymer.
8. Propylene polymer composition according to any of the preceding claims, wherein component (A) ranges from 58 to 72 wt% and component B ranges from 35 to 45 wt%.
9. The propylene polymer composition according to any of the preceding claims, wherein (T1) ranges from 28 to 72 wt% and T2 ranges from 28 to 72 wt%.
10. A polypropylene composition according to any one of the preceding claims, wherein The component (T2) has an amount of PP content ranging from 5 wt% to 10 wt% based on the total amount of the component (T2).
11. The polypropylene composition according to any one of the preceding claims, wherein component (T2) has a molecular weight of 0.940 g / cm 3 Up to 0.965g / cm 3 The polyurethane foam has a density in the range of 0.1 to 1.0 g / 10 min (ISO 1183-1) and a melt flow rate in the range of 0.1 to 1.0 g / 10 min (190°C / 2.16 kg ISO 1133-1).
12. Propylene polymer composition according to any of the preceding claims, wherein component (T1a) is a random copolymer of propylene containing from 1 to 6 wt% of ethylene derived units.
13. Propylene polymer composition according to any of the preceding claims, wherein component (T1b) is preferably selected from SBS and SEBS rubbers, which are (partially) hydrogenated styrene-(ethylene-butadiene)-styrene block copolymers.
14. The propylene polymer composition according to any one of the preceding claims, wherein component (T1c) is a propylene polymer comprising up to 30 wt% of C3-C 10 Ethylene polymers of alpha-olefins.
15. An extruded article obtained from the propylene polymer composition according to any of the preceding claims.
Citation Information
Patent Citations
Components and catalysts for the polymerization of olefins
EP0045977A2
Elastoplastic polyolefin compositions
EP0472946A2
Components and catalysts for the polymerization of olefins
US4522930A
Components and catalysts for the polymerization of olefins
WO2000063261A1
Components and catalysts for the polymerization of olefins
WO2001057099A1